Point-shear wave elastography generated by acoustic radiation force impulse in chronic pancreatitis - Wekerle, Maximilian; Murillo, Katharina; Boscamp, Manuel von; Hauber, Veronika; Ebert, Matthias; Antoni, Christoph Helmer; Hirth, Michael (United european gastroenterology journal, 2024)
Background Transcutaneous point-shear wave elastography (p-SWE) performed using an acoustic radiation force impulse can be used to quantify pancreatic stiffness in chronic pancreatitis (CP). We aimed to evaluate its usefulness to diagnose and monitor CP. Methods 175 participants were included in this prospective study including patients with CP (n = 65), liver cirrhosis (LC; n = 60), alcohol abuse (n = 10) and healthy controls (n = 40). Point-shear wave elastography of the pancreas was performed and quantified as median shear wave velocity (SWV). In the same way, p-SWE of the spleen served as a marker of portal hypertension. The M-ANNHEIM Severity score was used as global marker for disease activity in CP. Results Compared to healthy controls, pancreatic SWV was significantly elevated in CP (1.38 vs. 0.96 m/s; p < 0.0001, MWU-test). Pancreatic SWV was increased in alcoholic CP but not in hereditary CP. Receiver operating characteristic analysis revealed 1.2 m/s as the optimal cut-off to identify non-heredity-CP subjects (90% specificity; 81% sensitivity; 92% positive predictive value). Pancreatic SWV correlated significantly with the M-ANNHEIM Severity score, severity of CP-typical complications (both p < 0.05, linear regression analysis), morphological changes of the pancreas and need for hospital treatment (both p < 0.05, MWU-test) but not with exocrine or endocrine insufficiency. Pancreatic SWV >1.7 m/s was identified to predict M-ANNHEIM Severity score ≥11 points. Pancreatic SWV was also elevated in LC (1.42 m/s; p < 0.001), correlating with increased splenic SWV. Conclusion Transcutaneous pancreatic p-SWE represents a bedside, cost-effective and non-invasive tool which adds valuable information to the process of diagnosing and monitoring CP. By portal hypertension, an increased pancreatic SWV must be expected.